Analisis Pemahaman Konsep Matematika Pada Materi Bentuk Aljabar Setelah Pembelajaran Dengan Model Numbered Heads Together Siswa Kelas Vii Smp Swasta Rangga Rame - Thoma, Theresia Novita Yeli; Lede, Yulius Keremata; Napu, Timotius Woda; Making, Samuel Rex Mulyadi (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to evaluate the understanding of seventh-grade students at Rangga Rame Private Junior High School regarding mathematical concepts, particularly those related to algebraic expressions. Three seventh-grade students were selected for this qualitative descriptive study based on their conceptual knowledge test results. The ability levels of the three students are categorized as high, medium, and poor. Data collection techniques used structured interviews and tests. Data analysis techniques involved data reduction, data presentation, and data conclusion. The research results show that the differences in students' understanding of mathematical concepts result in grouping students into three levels. The indicators of conceptual understanding found include: the ability to explain concepts both verbally and in writing; grouping objects based on certain criteria; applying concepts procedurally; connecting concepts to solve problems; and presenting concepts in various representations, including graphs, tables, and diagrams. Eighteen students participated in the test; six of them were in the high group, four in the medium group, and the remaining six in the low group. The low level of knowledge is caused by several factors, including a lack of understanding of the questions, rushed answers, and inadequate mastery of the subject matter during the learning process.